Identification, structure elucidation and origin of a common pyridinium-thiocyanate intermediate in electrospray mass spectrometry among the benziamidazole-class proton pump inhibitors - Dong Sun; Chunyu Wang; Yanxia Fan; Jingkai Gu (Elsevier, 2023)
During the analysis of benziamidazole-class irreversible proton pump inhibitors, an unusual mass spectral response with the mass-to-charge ratio at [M+10]+ intrigued us, as it couldn't be assigned to any literature known relevant structure, intermediate or adduct ion. Moreover, this mysterious mass pattern of [M+10]+ has been gradually observed by series of marketed proton pump inhibitors, viz. omeprazole, pantoprazole, lansoprazole and rabeprazole. All the previous attempts to isolate the corresponding component were unsuccessful. The investigation of present work addresses this kind of signal to a pyridinium thiocyanate mass spectral intermediate (10), which is the common fragment ion of series of labile aggregates. The origin of such aggregates can be traced to the reactive intermediates formed by acid-promoted degradation. These reactive intermediates tend to react with each other and give raise series of complicated aggregates systematically in a water/acetonitrile solution by electrospray ionization. The structure of the corresponding pyridinium thiocyanate species of omeprazole (10a) has been eventually characterized with the help of synthetic specimen (10a'). Our structural proposal as well as its origin was supported by in situ nuclear magnetic resonance, chemical derivatization and colorimetric experiments.